2014
DOI: 10.1186/1749-8090-9-69
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholesterol levels and postoperative atrial fibrillation

Abstract: BackgroundPost-operative atrial fibrillation is an important complication after coronary bypass surgery. As inflammation and oxidative stress were makedly encountered in the etiology, high cholesterol was also defined to provoke atrial fibrillation. In this present study, the relationship between postoperative atrial fibrillation and preoperative serum lipid levels were evaluated.MethodsA total of 100 patients, who were operated at the department of Cardiovascular Surgery of our hospital were included to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
4
0
3
Order By: Relevance
“…Still, we showed that high LDL‐C levels were positively correlated with an increased risk of AF recurrence in patients undergoing RFCA. The result was consistent with a previous study investigating serum lipid levels with AF recurrence (Aydin et al, 2014). It suggested that the lower serum LDL‐C level in the preoperative period was associated with reduced risk of AF recurrence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Still, we showed that high LDL‐C levels were positively correlated with an increased risk of AF recurrence in patients undergoing RFCA. The result was consistent with a previous study investigating serum lipid levels with AF recurrence (Aydin et al, 2014). It suggested that the lower serum LDL‐C level in the preoperative period was associated with reduced risk of AF recurrence.…”
Section: Discussionsupporting
confidence: 93%
“…Those ion channel characteristics would influence Ca 2 accumulation in the cellular membrane, which is associated with AF initiation (Bastiaanse, Hold, & Van der Laarse, 1997; Saini, Arneja, & Dhalla, 2004). Decrease in LDL‐C levels by apheresis in patients with high serum LDL‐C levels has been shown to have a protective effect against the development of AF (Aydin et al, 2014). However, whether lipid‐lowering treatment reduces the risk of AF depends on different situations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, those patients tend A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 7 to have increased atrial conduit function, and evidence of left ventricular diastolic relaxation impairment compared to those without AF (Aytemir, Aksoyek, Ozer, Aslamaci, & Oto, 1999;Ferro, et al, 2009;Leung, Bellows, & Schiller, 2004;Maesen, et al, 2012;Nakai, et al, 2002;Nardi, et al, 2012). Other abnormalities that have been associated with increased incidence of POAF include high pre-operative levels of cholesterol (Aydin, et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Предполагается, что антиаритмический эффект проявляется посредством внутриклеточного гомеостаза кальция различными структурами статинов на разных уровнях, поскольку внутриклеточный мевалонатзависимый синтез холестерина ингибируется статинами. Низкий уровень холестерина в сыворотке замедляет внутриклеточное потребление ЛПНП, что обеспечивает стабильность клеточной мембраны и ингибирует электрическое ремоделирование, воздействуя на внутриклеточные уровни Ca [25].…”
Section: таблицаunclassified